2020
DOI: 10.3390/met10111527
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alloying Mn by Selective Laser Melting on the Microstructure and Biodegradation Properties of Pure Mg

Abstract: This work studied the effect of alloying Mn by selective laser melting on the microstructure and biodegradation properties of pure Mg. The grains in the microstructure were quasi-polygon in shape. The average grain size was similar (~10 μm) for the SLMed Mg-xMn with different Mn contents. The XPS spectra of the corrosion surface showed that alloying Mn into Mg by SLM produced a relatively protective manganese oxide film, which contributed to decreasing the biodegradation rate. All the results of the electroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…3f and Fig. 4f), as also observed by other researchers [56,57], which was probably caused by the large differences in the physical and mechanical properties between the Mg(OH) 2 film and MgF 2 [40] as well as the evolution of hydrogen during the fluoride conversion treatment.…”
Section: Surface Modificationsupporting
confidence: 78%
See 1 more Smart Citation
“…3f and Fig. 4f), as also observed by other researchers [56,57], which was probably caused by the large differences in the physical and mechanical properties between the Mg(OH) 2 film and MgF 2 [40] as well as the evolution of hydrogen during the fluoride conversion treatment.…”
Section: Surface Modificationsupporting
confidence: 78%
“…2e). However, the average grain size of the fabricated Mg scaffolds was larger than that of laser AM Mg [57] due to rapid cooling involved in the latter.…”
Section: Biomaterials Science Accepted Manuscriptmentioning
confidence: 89%
“…For instance, Shuai et al found that a 1 wt.% of Al additive remarkably reduced the grain size of LPBF-processed Mg-3Zn alloy from (21.6 ± 2.6) µm to (10.5 ± 1.9) µm, and with increasing the Al content to 7 wt.%, the grain size was further decreased to (6.8 ± 1.5) µm [79]. However, it is reported that the Mn addition had little impact on grain refinement [94]. The above phenomenon is ascribed to the undercooling degree variation with chemical composition addition.…”
Section: Microstructure Characteristicsmentioning
confidence: 94%
“…Chemical composition of material is another key factor affecting grain size. Up to now, the effects of Al [43,79], Mn [93][94][95], Zn [44], Cu [92,96], Ce [97], Dy [98] on the grain size of additively manufactured magnesium alloys have been investigated. The results demonstrated that the addition of Al, Cu, Zn, Ce and Dy can significantly refine the grains, and the grain size decreases monotonically with the content increase of these elements.…”
Section: Microstructure Characteristicsmentioning
confidence: 99%
“…The as-fabricated scaffolds showed improved biodegradation resistance of 0.17 ml/ cm 2 •day compared with the as-extruded and as-cast counterparts of 0.3 ml/cm 2 •day. Xie et al [104] investigated SLMed Mg-xMn with various content of Mn. The XPS spectra of the corrosion surface exhibited that alloying manganese into magnesium by SLM produced a protective film of manganese oxide, which reduced the biodegradation rate.…”
Section: Biodegradability Behaviormentioning
confidence: 99%